Identification of natural yellow, blue, green and black dyes in 15th-17th centuries Ottoman silk and wool textiles by HPLC with diode array detection - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2011)
High performance liquid chromatography coupled with diode array detection (HPLC-DAD) was utilised for the identification of dyestuffs in different plants such as dyers weld, gallnut, walloon oak, woad, indigo shrub and cochineal. The most important dyestuffs detected were natural yellow, green, beige, black and blue dyes which are found in historical textiles. In addition, reversed-phase HPLC with DAD was employed in the identification of natural dyes in extracts of historical silk art objects, from historical textiles and newly dyed silk fibres. The objects examined were from the 15th to 17th century Ottoman period and belong to the collection of the Topkapi Palace Museum in Istanbul. Fibres with yellow, blue, black, beige and green colours were selected for the analysis. Dye components were identified in the extracts of 11 art objects analysed; both insect and plant dyes were detected.
Keywords: art objects; dyestuff; ellagic acid; HPLC-diode array detection; indigotin; luteolin; PERFORMANCE LIQUID-CHROMATOGRAPHY; COPTIC TEXTILES; ANTHRAQUINONE